Pathways to Employment and Quality of Life for Apprenticeship and Traineeship Graduates with Disabilities - Cocks, Errol; Thoresen, Stian; Lee, Elinda (Routledge, 2015)
People with disabilities have low participation rates in employment and vocational education and training. Thirty adults with disabilities were sampled from an Australian longitudinal study of economic and social outcomes achieved by graduate apprentices and trainees. Participants were surveyed and interviewed to identify pathways from high school to 12-months post-graduation and completed the Quality of Life Questionnaire (QOL.Q). Career pathways incorporated experiences facilitating career development including continuous engagement in vocational activities and support from school personnel and external disability agencies. A year following graduation, 87% were in paid work, 53% remained with the training employer, and 40% continued with vocational education. Positive quality of life (QoL) outcomes were associated with employment, employee benefits and satisfaction with work and social connections. Our research demonstrated that apprenticeships and traineeships led to positive graduate employment outcomes and career pathways for adults with disabilities. Positive employment outcomes were associated with enhanced QoL for participants.